STUDI TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA FKIP UNIVERSITAS JEMBER - Oktavianingtyas, Ervin (KadikmA, 2013)
Abstract.The purpose of this research to determine the factors affecting student achievement and the most dominant factor, especially in Mathematics Education Program of FKIP in Jember University. The populations of this research were all students of class 2005, 2006, and 2007 at Mathematics Education Program in Jember University that were 318 students, 178students as samples. This research used two variables: the independent variable (intrinsic motivation, extrinsic motivation, methods of learning, teaching methods,use of leisure time, physical learning environment, family economic circumstances, and physical factors) and the dependent variable (student achievement). The collecting technique data used were questionnaires and documentary. Based on logistic regression analysis obtained extrinsic factors, physical learning environment, family economic circumstances, and physical factors having significant influences and the most dominant factor was physical learning environment variables, where as intrinsic motivation factors, learning method, teaching methods, and theuse of leisure time werenât significantin determining student achievement. Key Words: students achievement